Honeypot Integration with Software-Defined Networking (SDN) for DDoS Attack Mitigation - Sugiyatno (University of Respati Yogyakarta, Indonesia, 2025)
Distributed Denial of Service (DDoS) attacks are one of the serious threats in cybersecurity that can disrupt the availability of network services. Traditional approaches to DDoS mitigation often have limitations in detecting complex attack patterns and responding dynamically. This research aims to develop a framework that integrates Honeypot with Software-Defined Networking (SDN) to improve the ability to adaptively mitigate DDoS attacks. The SDN approach was chosen due to its unique ability to provide centralized network control and high flexibility in real-time traffic management. The research method involves developing a prototype of Honeypot-SDN integration, testing through simulation using Mininet, as well as analyzing network traffic data using machine learning algorithms. Data obtained from simulated DDoS attacks with various scenarios, including variations in attack intensity and type, were analyzed to test the effectiveness of the system.